TUNA SATAK BATHI SANAK (KEARIFAN JAWA DALAM ETIKA BISNIS) - Pitoyo, Djoko (Jurnal Filsafat "WISDOM", 2008)
AbstractThis library research is tended to search for the Javanesewisdom in a business scope. The object of this research includes, first, genuine Javanese manuscripts containing moral and spiritual teachings that most of them are in the form of lyrical serat, tembang, saloka, paribasan, parikan, or wangsalan; second, essays written by many experts about the Javanese philosophy including literary, sociological, anthropological, as well as philosophical studies; and third, the oral statement in daily’ conversation in Java.Those materials are explored and identified by focusing onthe Javanese values that are relevant to the business world. These values are then analyzed explicitly and interpreted, systemized or reconstructed and formulated to build a frame of values that is coherent and clear. Afterwards, there will be a critical review to find out their strengths and weaknesses.This research is conducted to prove that the Javaneseculture possesses many wise values that are relevant to thebusiness world. Those are the principles of determination, hardworking, thoughtfulness, smartness, accuracy, judge fullness, creativity, being cautious, and spendrift, controlling lust and passion, pursuing new information and knowledge, fair in doing the transaction, building a good relationship with the stakeholders, and having a high social responsibility.Keywords: business, Javanese wisdom, morality.